2009
DOI: 10.1016/j.cell.2009.04.028
|View full text |Cite
|
Sign up to set email alerts
|

An Effector of RNA-Directed DNA Methylation in Arabidopsis Is an ARGONAUTE 4- and RNA-Binding Protein

Abstract: Summary DNA methylation is a conserved epigenetic mark in plants and mammals. In Arabidopsis, DNA methylation can be triggered by small interfering RNAs (siRNAs) through an RNA-directed DNA methylation (RdDM) pathway. Here we report the identification of a new RdDM effector, RDM3/KTF1. Loss-of-function mutations in RDM3/KTF1 reduce DNA methylation and release the silencing of RdDM target loci without abolishing the siRNA triggers. KTF1 has similarity to the transcription elongation factor SPT5 and contains a C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
240
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 241 publications
(252 citation statements)
references
References 44 publications
8
240
0
4
Order By: Relevance
“…The AGO4/siRNA complexes are recruited to target loci via base-pairing with scaffold transcripts generated by RNA polymerase Pol V (Pontier et al, 2005;Mosher et al, 2008;Wierzbicki et al, 2008Wierzbicki et al, , 2009). The recruitment of AGO4 to chromatin may also be facilitated by its interaction with the GW/WGrich extensions of NRPE1 (the largest subunit of Pol V) Pontes et al, 2006;El-Shami et al, 2007;Li et al, 2008) and KTF1/SPT5L (a transcription elongation factor) (Bies-Etheve et al, 2009;He et al, 2009). The conserved GW/WG motif, defining an "Ago hook," is widely present in factors implicated in AGO actions (Azevedo et al, 2011;Garcia et al, 2012;Pontier et al, 2012).…”
Section: Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…The AGO4/siRNA complexes are recruited to target loci via base-pairing with scaffold transcripts generated by RNA polymerase Pol V (Pontier et al, 2005;Mosher et al, 2008;Wierzbicki et al, 2008Wierzbicki et al, , 2009). The recruitment of AGO4 to chromatin may also be facilitated by its interaction with the GW/WGrich extensions of NRPE1 (the largest subunit of Pol V) Pontes et al, 2006;El-Shami et al, 2007;Li et al, 2008) and KTF1/SPT5L (a transcription elongation factor) (Bies-Etheve et al, 2009;He et al, 2009). The conserved GW/WG motif, defining an "Ago hook," is widely present in factors implicated in AGO actions (Azevedo et al, 2011;Garcia et al, 2012;Pontier et al, 2012).…”
Section: Dna Methylationmentioning
confidence: 99%
“…In plants, DNA methylation can be mediated by AGO4-bound hc-siRNAs through a specialized RNAi pathway termed RNA-directed DNA methylation (RdDM). RdDM entails the generation of double-stranded RNAs (dsRNAs) by coordinated activities of RNA Polymerase IV (Pol IV) and RNAdependent RNA polymerase 2 (RDR2) (Xie et al, 2004;Herr et al, 2005;Kanno et al, 2005;Onodera et al, 2005;Li et al, 2008;He et al, 2009;Haag et al, 2012). dsRNAs are then processed by DCL3 to produce 24-nucleotide hc-siRNAs (Xie et al, 2004).…”
Section: Dna Methylationmentioning
confidence: 99%
“…ROS1 is a key DNA demethylation component in vegetative tissues (9), and its transcript level is regulated by MET1 and several RdDM components (10). Screening for second-site suppressors of ros1 mutants by using silenced RD29A-LUC has enabled researchers to identify the main components of the RdDM pathway and has further indicated that RdDM and ROS1 antagonistically regulate DNA methylation (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…The 24-nt siRNAs are loaded onto ARGONAUTE proteins AGO4 and/or AGO6 (Zheng et al 2007;Matzke et al 2009) and target genomic regions, possibly by base-pairing with nascent Pol V transcripts from the target loci. The Pol V-dependent RNA transcripts are tethered to AGO4 by the action of KTF1, forming an effector complex containing AGO4, KTF1, Pol V-dependent transcripts, and siRNAs (He et al 2009a). The effector complex directs DRM2 for de novo methylation of target genomic sequences.…”
mentioning
confidence: 99%